Counting statistics of single electron transport in bilayer graphene quantum dots - Rebekka Garreis; Jonas Daniel Gerber; Veronika Stará; Chuyao Tong; Carolin Gold; Marc Röösli; Kenji Watanabe; Takashi Taniguchi; Klaus Ensslin; Thomas Ihn; Annika Kurzmann (Physical Review Research, 2023)
We measure telegraph noise of current fluctuations in an electrostatically defined quantum dot in bilayer graphene by real-time detection of single electron tunneling with a capacitively coupled neighboring quantum dot. Suppression of the second and third cumulant (related to shot noise) in a tunable graphene quantum dot is demonstrated experimentally. With this method we demonstrate the ability to measure very low current and noise levels. Furthermore, we use this method to investigate the first spin excited state, an essential prerequisite to measure spin relaxation.